The role of laser power and frequency on metal surfaces of adhesive bridge in increasing the bond strength of resin cement - Munte, Winnie; Ritonga, Putri Welda Utami; Tamin, Haslinda Z. (Indonesia Prosthodontic Association, 2024)
Background Adhesive Bridge is a fixed denture that is attached to the tooth structure, especially the enamel, which has been etched to achieve micromechanical retention. Among other things, adhesive bridge attachment depends on, one important factor is the adhesive bond between the etched enamel and the retained metal. To increase the retention of adhesive bridges, variations of micromechanical surface treatment on metal can be carried out in the form of chemical or electrical etching, air particle abrasion (sandblasting), primary metal, tin plating, silica coating, and lasers. Objective Lasers with different energies, strengths, frequencies, wavelengths, durations and distances can create a thin layer of porous oxide which increases the bonding strength of resin cement for adhesive bridges. The role of laser power and frequency as well as the selection of the right type of resin on the metal surface of the adhesive bridge can increase the bonding strength of the resin cement on the adhesive bridge. Conclusion The selection of the type of surface treatment such as laser and the right type of resin cement can affect the bond strength of the resin cement on the adhesive bridge.